Developing sport for women and girls - Sherry, Emma; Rowe, Katie; Routledge (Firm) (London : New York : Routledge, 2020)
"Women and girls are often excluded from organised sport or face challenges in accessing sport or developing within sport. This is the first book to focus on sport development for women and girls. It provides a theoretical and practical framework for readers in the emerging field of sport development. Developing Sport for Women and Girls examines both the development of sport, and development through sport with expert contributions from Australasia, North America, and Europe. It offers critical analysis of contemporary sport development, from high performance pathways to engaging diverse communities to the use of sport to empower women and girls. Each chapter explores various contexts of sport development and sport for development theory with a specific focus on women and girls. It covers key topics such as health, education, sexual orientation and participation across the lifecourse, and features international case studies in every chapter. This is essential reading for students, academics, researchers and practitioners working in the area of sport development or sport management"--
OCLC-licensed vendor bibliographic record.
Keywords: Sports for women; Sports for girls; Sports administration; SPORTS & RECREATION / General; SPORTS & RECREATION / Coaching / General; SPORTS & RECREATION / Sociology of Sports